Les stratégies des acteurs intermédiaires des circuits alimentaires de proximité en Guadeloupe : vers une alimentation relocalisée ? - Valérie Angeon; Sandrine Fréguin-Gresh (EchoGéo)
This article analyses the role of intermediary actors in the food system in terms of proximity in Guadeloupe. Three main food circuits are studied: open-air markets, farmers' markets and supermarkets. The results show that, depending on the circuit, the dimensions of proximity are differently mobilized. In the three cases studied, the intermediary actors play a pivotal role, but do not contribute similarly to the relocalization of food. Despite the existing windows of opportunity, no real territorial project has emerged that could engage all the stakeholders of the food system.